The Influence of the TPACK Approach Based on Canva and Quizizz Media on Students’ Learning Motivation - Istikazah Martiana, Lubna, Wildan (Lembaga Bale Literasi, 2025)
This study aims to analyze the influence of the media-based TPACK approach. Canva and Quizizz on the learning motivation of class XI students in the subject of the Qur'an Hadith MA Al-Hasani Ma'arif. This research uses quantitative methods, specifically a pre-experimental one-group pretest-posttest design, with a research sample of 22 students. The data collection technique in this study used a questionnaire to measure students' learning motivation. Based on the processing of the data obtained by using the Paired Sample T-Test, a significant value of 0.000 was obtained. with a significance level (0.05), so it can be stated that H0 is rejected and Ha is accepted. It can be concluded that the TPACK approach, based on Canva media and Quizizz, influences the learning motivation of class XI students in the subject of Al-Qur'an Hadith at MA Al-Hasani Ma'arif